What's new in consolidation therapy in AML? - Schlenk, Richard Friedrich; Jaramillo Segura, Sonia; Müller-Tidow, Carsten (ScienceDirect. [Elsevier journals]. [Cell Press journals collection], 2019)
Intensive induction chemotherapy followed by postremission treatment with either high-dose cytarabine-based regimens, autologous or allogeneic hematopoietic stem cell transplantation is still recognized as the main road toward cure in acute myeloid leukemia (AML). Pretreatment risk classification remains a key determinant of type and intensity of post-remission therapy. Still, high-dose cytarabine-based consolidation therapy is a cornerstone of postremission therapy with some recent adjustments regarding dosage and schedule. Current approvals of midostaurin, gemtuzumab ozogamicin, CPX-351, and ivosidenib as well as enasidenib comprise induction as well as consolidation therapy. In recent years measurable residual disease assessment is increasingly used to dynamically fine tune treatment during postremission treatment.